“Precision” Public Health — Between Novelty and Hype - Chowkwanyun, Merlin; Bayer, Ronald; Galea, Sandro (The New England journal of medicine, 2018)
Does the turn toward “precision” public health offer the opportunity for a reconceptualized, empowered public health enterprise — or might it represent an abandonment of the traditional mission of enhancing population well-being? And how novel is it, anyway?